KORELASI ANTARA MOTIVASI DAN KEDISIPLINAN SISWA DENGAN PEROLEHAN BELAJAR PKn SEKOLAH DASAR NEGERI PONTIANAK - Mubarokah, Zaidahtul; Sabri, Tahmid; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe general problem in this study is "Is it related to motivation and discipline with learning outcomes in learning Citizenship Education class V 15 South Pontianak State Elementary School?". This research uses a descriptive method with a form of relationship study research. The population as well as the sample are all grade V students issued by 23 people consisting of one class. Sampling uses Nonprobability sampling technique with saturated sampling type. Data collection techniques and tools used are indirect communication with data collection tools in the form of questionnaires and documentary study techniques, which are data collection tools in the form of even semester report cards on Civics Education subjects. The results showed that motivation in South Pontianak 15 Elementary School was classified as very good at 88.17%, discipline in 15 Pontianak South Elementary School was classified as very good at 87.52%, and learning outcomes in the Civics Education lesson obtained an average value of an average of 82.83. The average between motivation and discipline of learning with student learning outcomes of 0.483 then the value compared with rtable at the level of 5% for N = 24 is 0.404. Thus r count> from r table or 0.483> 0.404, then Ha is accepted. Significant learning between motivation and discipline with learning outcomes in learning Citizenship Education class V 15 Primary School South Pontianak.Â Keywords: Citizenship Education , Discipline, learning outcomes, Motivation.